Cancer-associated circulating large extracellular vesicles in cholangiocarcinoma and hepatocellular carcinoma - Julich-Haertel, Henrike; Urban, Sabine K.; Krawczyk, Marcin; Willms, Arnulf; Jankowski, Krzysztof; Patkowski, Waldemar; Kruk, Beata; Krasnodębski, Maciej; Ligocka, Joanna; Schwab, Robert; Richardsen, Ines; Schaaf, Sebastian; et al. (Journal of hepatology, 2017)
[Display omitted] Large extracellular vesicles, specifically AnnexinV+ EpCAM+ CD147+ tumour-associated microparticles (taMPs), facilitate the detection of colorectal carcinoma (CRC), non-small cell lung carcinoma (NSCLC) as well as pancreas carcinoma (PaCa). Here we assess the diagnostic value of taMPs for detection and monitoring of hepatocellular carcinoma (HCC) and cholangiocarcinoma (CCA). Specifically, the aim of this study was to differentiate liver taMPs from other cancer taMPs, such as CRC and NSCLC. Fluorescence-activated cell scanning (FACS) was applied to detect various taMP populations in patients’ sera that were associated with the presence of a tumour (AnnexinV+ EpCAM+ CD147+ taMPs) or could discriminate between cirrhosis (due to HCV or HBV) and liver cancers (AnnexinV+ EpCAM+ ASGPR1+ taMPs). In total 172 patients with liver cancer (HCC or CCA), 54 with cirrhosis and no liver neoplasia, and 202 control subjects were enrolled. The results indicate that AnnexinV+ EpCAM+ CD147+ taMPs were elevated in HCC and CCA. Furthermore, AnnexinV+ EpCAM+ ASGPR1+ CD133+ taMPs allowed the distinction of liver malignancies (HCC or CCA) and cirrhosis from tumour-free individuals and, more importantly, from patients carrying other non-liver cancers. In addition, AnnexinV+ EpCAM+ ASGPR1+ taMPs were increased in liver cancer-bearing patients compared to patients with cirrhosis that lacked any detectable liver malignancy. The smallest sizes of successfully detected cancers were ranging between 11–15mm. AnnexinV+ EpCAM+ ASGPR1+ taMPs decreased at 7days after curative R0 tumour resection suggesting close correlations with tumour presence. ROC values, sensitivity/specificity scores and positive/negative predictive values (>78%) indicated a potent diagnostic accuracy of AnnexinV+ EpCAM+ ASGPR1+ taMPs. These data provide strong evidence that AnnexinV+ EpCAM+ ASGPR1+ taMPs are a novel biomarker of HCC and CCA liquid biopsy that permit a non-invasive assessment of the presence and possible extent of these cancers in patients with advanced liver diseases. Microparticles (MPs) are small vesicles that bleb from the membrane of every cell, including cancer cells, and are released to circulate in the bloodstream. Since their surface composition is similar to the surface of their underlying parental cell, MPs from the bloodstream can be isolated and by screening their surface components, the presence of their parental cells can be identified. This way, it was possible to detect and discriminate between patients bearing liver cancer and chronic liver cirrhosis.